Benchmarking Firm-level Resources, Capabilities, and Postures Driving Export Performance of SMEs - Robert Celec; Dietfried Globocnik (Naše gospodarstvo/Our economy, 2017)
This paper aimed to identify success factors of export performance for small and medium-sized enterprises (SMEs). Drawing on the resource-based view, the dynamic capability view, and international entrepreneurship theory, we extracted relevant assets, capabilities, and postures at the firm level. An extended benchmarking method was applied to empirically test the proposed success factors with a cross-sectional sample of 99 Slovenian SMEs. The results highlight the crucial role of management competence, financial and human resources, market orientation, negotiation flexibility, and a proactive and risk-taking posture to achieve superior export performance.